Análisis del tratamiento de la divulgación científica publicada en los medios nativos digitales Primer Reporte y Lo del Momento Loja (enero 2020 – junio 2022). - Romero Ayora, Lisbette Estefania (2023)
In the field of research, scientific dissemination enhances development and its impact on society. Therefore, according to numerous studies, it is necessary to use traditional and digital scenarios. The main purpose of this research was to analyze the scientific dissemination of information published in the digital native media Primer Reporte and Lo del Momento Loja. Therefore, the study focuses on identifying and analyzing the characteristics of dissemination, the treatment of content and dissemination mechanisms presented by digital media. The mixed approach used allowed, from a broad perspective, to collect, interpret, systematically review, develop contrasts and link data between the web observation matrices and the interviews conducted with experts. The results point out the need to train journalists specialized in scientific dissemination issues, since the information published in the digital native media Primer Reporte and Lo del Momento Loja is incipient and does not meet the appropriate characteristics to transmit complex ideas to the audience in a simple way, without losing accuracy. Keywords: science popularization, science journalism, digital media, news information.